2059. Antimicrobial Stewardship of Community Parenteral Antimicrobial Therapy: A Health System Approach - Buckel, Whitney R (Open Forum Infect Dis, 2019)
BACKGROUND: Community parenteral antimicrobial therapy (CoPAT) allows patients to receive intravenous (IV) antimicrobials outside the hospital; however, inappropriate use occurs and can lead to adverse outcomes. In addition, these patients are at high risk of readmission. Our objective was to assess the quality of CoPAT in a large healthcare system in order to guide implementation of an intervention requiring mandatory review by antimicrobial stewardship. METHODS: We identified patients with orders for IV antimicrobials at discharge between January 1 and December 10, 2018. Patients were excluded if transferred to an acute care facility, left against medical advice, or died. 250 patients were selected using a random number generator and reviewed consecutively until 100 confirmed CoPAT encounters were identified. Each encounter was evaluated for evidence of ID consultation, opportunities for stewardship interventions in seven categories (See Table 1), and adverse events such as emergency room (ER) visits and readmissions. RESULTS: The query identified 4,642 potential CoPAT discharges from 22 hospitals (see Table 2). 117 encounters were reviewed to reach 100 true CoPAT discharges (85% query accuracy). Of these, 55 (55%) received a formal ID consult, 6 (6%) had an ID pharmacist or ID physician curbside, and 5 (5%) had an ID clinic follow-up appointment scheduled without formal ID consult. Opportunity for stewardship intervention was found in 50 (50%) patients (see Table 1). There were 31 (31%) patients who were seen in the ER (n = 21) and/or re-admitted (n = 19) to the hospital during or shortly after completion of CoPAT, of which 25 (81%) were potentially related to CoPAT, including abnormal laboratory findings, PICC-line complications, and signs or symptoms of infection. CONCLUSION: CoPAT patients are complex with high healthcare utilization. Mandatory ID review of patients receiving CoPAT has the potential to impact 2,000 lives annually in a large health system. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.